Maqashid Syariah and Consumer Protection: Rebuilding Gen Z Trust in Sharia Insurance - Najma Taralia Farah; Joko Setyono; Samsul Hadi; Navi Risanti; Fattah S. Santoso; Ali Sayyid Mata (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2027)
This normative legal research examines why Generation Z remains hesitant toward sharia insurance despite growing digital literacy and relatively high religiosity. Within conceptual and statutory approach, it argues that low Islamic financial literacy, information overload, and the gap between normative sharia principles and actual industry practice are the main factors undermining trust. Framed through the lens of maqashid syariah, the study finds that trust cannot be built on religious labelling requires tangible evidence of transparency, fair governance, and real-world benefits. Strengthening digital literacy programmes, improving product transparency, and anchoring institutional governance in measurable maqashid indicators are proposed as concrete steps toward rebuilding Generation Z’s confidence in sharia insurance.